Serum and blister‐fluid elevation and decreased epidermal content of high‐mobility group box 1 protein in drug‐induced Stevens–Johnson syndrome/toxic epidermal necrolysis. (1st July 2019) - Carr, D.F.; Wang, C.‐W.; Bellón, T.; Ressel, L.; Nwikue, G.; Shrivastava, V.; Bergfeld, W.; Jorgensen, A.L.; Chung, W.‐H.; Pirmohamed, M.
Summary: Background: High‐mobility group box 1 (HMGB1) is a damage‐associated molecular‐pattern protein. Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) are serious, immune‐mediated skin‐blistering conditions. Objectives: To determine serum and/or blister‐fluid total HMGB1 levels in SJS/TEN cohorts, and HMGB1 expression in formalin‐fixed, paraffin‐embedded (FFPE) SJS/TEN skin vs. healthy and maculopapular exanthema (MPE) skin. Methods Serum HMGB1 was quantified in Malawian nevirapine‐induced hypersensitivity, Taiwanese SJS/TEN and Spanish SJS/TEN cohorts. FFPE skin (healthy skin, MPE, SJS/TEN) was stained and assessed for HMGB1 expression. Results: Serum total HMGB1 was not significantly elevated in patients with nevirapine‐induced SJS/TEN (3·98 ± 2·17 ng mL −1 ), MPE (3·92 ± 2·75 ng mL −1 ) or drug reaction with eosinophilia and systemic symptoms (4·73 ± 3·00 ng mL −1 ) vs. tolerant controls (2·97 ± 3·00 ng mL −1 ). HMGB1 was significantly elevated in Taiwanese patients with SJS/TEN, highest during the acute phase (32·6 ± 26·6 ng mL −1 ) vs. the maximal (19·7 ± 23·2 ng mL −1 ; P = 0·007) and recovery (24·6 ± 25·3 ng mL −1 ; P = 0·027) phases. In blister fluid from Spanish patients with SJS/TEN, HMGB1 (486·8 ± 687·9 ng mL −1 ) was significantly higher than in serum (8·8 ± 7·6 ng mL −1 ; P <0·001). Preblistered SJS/TEN skin showed decreased epidermal nuclear HMGB1 expression in upper epidermis vs. healthy or MPE skin but retained basal/suprabasal expression. Conclusions: Epidermal HMGB1 expression was decreased in SJS/TEN skin. Retained basal/suprabasal epidermal HMGB1 expression may exacerbate localized injury in SJS/TEN.